(untitled) (Research, Society and Development, 2020)
This article aims to evaluate the total phenolics and antioxidant activity of the prepared extract of the fungus Penicillium purpurogenum, obtained from a polluted marine environment of São Luís-MA. The research was carried out at Laguna da Jansen located in the Municipality of São Luís, Maranhão, Brazil. Four sediment collections were performed from May to September 2017, in the morning period. The samples were obtained from a depth of up to 73.5 cm with the aid of a metal dredger. The identification of the fungus followed methodologies of isolation and subsequent preparation of the extracts with evaluation of total phenolics by the Folin-Ciocalteu method and antioxidant activity by the DPPH radical sequestration method. Identification confirmed the presence of Penicillium purpurogenum. The extracts of P. purpurogenum varied in the quantification of total phenolics of 791.00 mg EAT g-1 for FR1 extract and 650.82 mg EAT g-1 for FR2. In antioxidant activity, wecould verify that the EC50 found in the FR1 extract was 22.59 μg mL-1 and FR2 39.80 μg mL-1. Concluding that the EXTRACT FR2 showed strong antioxidant activity while FR1 was very strong by the DPPH radical method.